ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING (2019-2021) - Sintia, Siti Amina Ratna; Sari, Lita Permata; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Investment decisions and appropriate funding decisions can effect company profits and the distribution of dividends to shareholders and firm value. The purpose of this study is to analyze and examine factors Influencing firm value in food and beverage companies listed on the Indonesia Stock Exchange with dividend policy as an intervening variable (2019-2021). The population in this study are all food and beverage companies that have listed on the Indonesia Stock Exchange during 2019-2021 period, totaling 72 companies. The sampling technique is determined by purposive sampling. Data analysis and hypothesis test of this study use Partial Least Square – Structural Equation Modeling (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that investment decisions have a significant positive effect on dividend policy, funding decisions have an insignificant negative effect on dividend policy, investment decisions have a significant positive effect on firm value, funding decisions have an significant negative effect on firm value, dividend policy has an insignificant positive effect on firm value. The results of the indirect effect hypothesis test show that the investment decisions variable has a significant positive effect on firm value through dividend policy, funding decisions have an insignificant negative effect on firm value through dividend policy.